TO DETERMINE THE INCIDENCE, RISK FACTORS, AND OUTCOMES FOR DELAYED STERNAL CLOSURE IN CHILDREN WITH CONGENITAL HEART DISEASES UNDERGOING OPEN HEART SURGERIES (The Research of Medical Science Review, 2024)
Delayed sternal closure (DSC) is an important strategy to stabilize hemodynamic instability in the early postoperative period in children after congenital heart surgery. Although stabilizing inadequate hemodynamics, open sternal management for prolonged periods may lead to complications and higher rates of perioperative morbidity, in addition to increased early and late mortality. The purpose of this study was to evaluate the incidence, risk factors potentially modifiable, and postoperative outcomes of DSC in children undergoing open-heart surgery for congenital heart defects. Inclusion criteria were any pediatric patient undergoing surgery for TOF, ASD, VSD and complex congenital heart diseases. The primary outcomes investigated were the occurrence of DSC, duration of stay in the intensive care unit (ICU), duration of mechanical ventilation (MV), and postoperative complications. Statistical analysis performed with SPSS revealed major DSC risk factor elements as poor Left Ventricular Ejection Fraction (LVEF) of 53.93 ± 10.99, poor Tricuspid Annular Plane Systolic Excursion (TAPSE) of 10.86 ±3.95, and blood gas values (poor PCO2 of 33.78 ± 2.76 and PO2 of 176.23 ± 76.65) which were identified as strong predictors of DSC. Also, a history of previous surgery was significantly associated with an increased risk of DSC. However, the study also emphasizes the need for early identification of these risk factors to optimize postoperative care and achieve better clinical outcomes.